2018
DOI: 10.3130/aije.83.543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulated Work in Artificial Climate Chamber on Physiological and Psychological Responses of Construction Workers With Air-Conditioned Wear

Abstract: To extract the effects of air-conditioned wear (ACW), we carried out experiments to measure the physiological and psychological responses of workers performing simulated construction work in an artificial climate chamber at controlled room temperatures of 29 and 34. The workers wore ACW or not. The effects of wearing ACW on skin temperature, sublingual temperatures, sweat rate and heart rate were significant only at 34. We propose that the heart rate varies due to sweat content of clothing reflecting dehydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…It is possible that such a complex thermal discomfort sensation can be estimated using the CVRR. A previous study [19] reported that the CVRR is significantly higher when wearing work wear with a fan to prevent heat stroke than when wearing work wear without a fan. The CVRR is therefore an index of comfort related to stuffiness and thermal stimulus.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that such a complex thermal discomfort sensation can be estimated using the CVRR. A previous study [19] reported that the CVRR is significantly higher when wearing work wear with a fan to prevent heat stroke than when wearing work wear without a fan. The CVRR is therefore an index of comfort related to stuffiness and thermal stimulus.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, since the occupations that were measured at the CS (FWs and RPs) were the same as the occupations in AC experiments, the relationship between the ER and rate of naked BWL of CWs wearing/not wearing VWW was determined based on the results of the AC experiment. 7 The rate of naked BWL (sweat rate + insensible perspiration), which is difficult to measure at the CS, was estimated from the regression formula and the effects of wearing/not wearing VWW and WS on the rate of naked BWL were evaluated. Figure 3 shows the measurement results of the thermal environment on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CWs working late in the afternoon are particularly prone to dehydration. The results estimated from the path model of Yamazaki et al 7 revealed that the HR during PM2 was approximately 6 bpm higher than that during AM1. The higher HR during PM2 caused the MST to be 0.7°C higher in PM1 and 0.6°C higher in PM2 compared to that in AM1 (F(1, 3) = 3.899, P < .05) and the sublingual temperature to be 0.3°C higher in PM1 and PM2 than in AM1 (F(1, 3) = 2.837, P < .05) as indicated in Figure 7.…”
Section: Effects Of Vww and Ws On The Rate Of Naked Bwlmentioning
confidence: 93%
See 2 more Smart Citations